Clinical characteristics and genomic epidemiological survey of tuberculosis in Wuzhou, China, 2022 - Jianpeng Li; Manman Zhao; Weidao Huang; Xuanxuan Huang; Yongqiang Ou (Microbiology Spectrum)
ABSTRACT Tuberculosis (TB) is a serious respiratory disease posing significant public health threats, such as the variation in Mycobacterium tuberculosis (M.tb) lineages and their associated drug resistance across regions. In 2022, clinical data and culture-positive TB samples were collected from the Third People’s Hospital in Wuzhou, China. M.tb drug resistance and lineage were analyzed using whole-genome sequencing, while logistic regression was applied to identify factors influencing patient outcomes. Among 169 strains analyzed, an overall drug resistance rate of 23.1% was observed. Multidrug-resistant or rifampicin-resistant cases constituted 7.7% of the strains. Most strains belonged to lineage 2 (69.8%), followed by lineage 4 (27.8%). Poor treatment adherence, being aged 65 or older, and retreatment emerged as risk factors for unfavorable outcomes. This pioneering survey provides crucial insights into TB patient characteristics, drug resistance patterns, and lineage distribution in Wuzhou, laying a foundation for future targeted TB control strategies in the region.IMPORTANCEIn 2022, tuberculosis (TB) was the second leading cause of death from a single infectious agent worldwide, posing a serious threat to global health. The epidemiological characteristics of TB vary considerably from country to country, and even from region to region within a single country, due to differences in the economy, medical conditions, education, and other factors. Understanding the current status of TB epidemics in the region is important, with practical implications for local diagnosis, treatment, and control. This genomic epidemiological survey has provided a first insight into the characteristics of TB patients, drug resistance rates, prevalence lineage, and factors associated with unfavorable outcomes in Wuzhou, China.